2020
DOI: 10.1111/mcn.13076
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anaemia among Ghanaian women and children vary by population group and climate zone

Abstract: Anaemia has serious effects on human health and has multifactorial aetiologies. This study aimed to determine putative risk factors for anaemia in children 6-59 months and 15-to 49-year-old non-pregnant women living in Ghana. Data from a nationally representative cross-sectional survey were analysed for associations between anaemia and various anaemia risk factors. National and stratum-specific multivariable regressions were constructed separately for children and women to calculate the adjusted prevalence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
2
16
0
2
Order By: Relevance
“…Almost forty percent of children had elevated CRP or AGP concentrations, indicative of inflammatory responses to infection. These results alongside the finding that CRP and AGP were strongly correlated with Hb concentrations suggest that anemia in this sample is in part attributable to infectious factors, in agreement with recent studies of anemia in Ghanaian children [10,11]. As has been found in other studies investigating the burden of enteropathogens among children in LMICs, most children (87.0%) in this study had at least one bacterial enteropathogen detected in their stool, with EAEC and aEPEC being the most prevalent [20,47].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Almost forty percent of children had elevated CRP or AGP concentrations, indicative of inflammatory responses to infection. These results alongside the finding that CRP and AGP were strongly correlated with Hb concentrations suggest that anemia in this sample is in part attributable to infectious factors, in agreement with recent studies of anemia in Ghanaian children [10,11]. As has been found in other studies investigating the burden of enteropathogens among children in LMICs, most children (87.0%) in this study had at least one bacterial enteropathogen detected in their stool, with EAEC and aEPEC being the most prevalent [20,47].…”
Section: Discussionsupporting
confidence: 92%
“…Analysis of the 2017 Ghana Micronutrient Survey found that only 35% of total anemia in 6-59-month-old children was associated with iron deficiency [10]. In the Southern Belt of Ghana, where our study took place, anemia was neither associated with children's iron status nor vitamin A deficiency [11]. Indeed, three-quarters of the anemia burden was attributable to factors associated with infectious diseases (i.e., malaria, inflammation, and fever) [11].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Given the multiple causes of anemia (inflammations due to infections, low dietary intake of iron and other micronutrients, inherited blood disorders) in Ghana, context-specific determinants of anemia are required to guide appropriate interventions. For instance, Petry et al showed that while iron deficiency was associated with children being anemic in the Northern and Middle belts of Ghana, there was no such relationship among children in the Southern Belt [ 52 ]. Lopes et al suggested in their systematic review of nutrition-specific interventions for preventing and controlling anemia that besides the continuous efforts to improve dietary diversity and quality, daily iron supplementation may increase the hemoglobin levels and decrease the risk of anemia in both non-pregnant and pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that the peak of anaemia in 2008 was highest in the forest zone (not shown), which was contrary to other studies in Ghana (15,54) . The forest zone of Ghana has a tropical climate in which malaria exposure is higher (55) ; although we could not verify this with the available data, a recent study found that while anaemia in children and reproductive women was associated with iron deficiency in northern Ghana (Guinea savannah zone), it was rather associated with inflammation in the middle and southern belts (forest zone) of the country (56) .…”
Section: Discussionmentioning
confidence: 71%